Pendidikan Multikultural sebagai Pendekatan Misi dalam Program Remaja Teladan (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
Indonesia has a diversity of ethnicities, religions, races and cultures that must be maintained for the sake of unity. Multicultural education is important to instill the value of tolerance and respect for differences. This research focuses on the effectiveness of multicultural education in the Exemplary Teenager program in the Christian Evangelical Church in Minahasa, especially in the Southwest Manado Region. The method used is qualitative with observation and interviews. The results show that there are social interactions that reflect tolerance, but the understanding of multicultural education is still minimal. The program focuses more on faith and moral development without integrated multicultural materials. To improve effectiveness, a curriculum that teaches tolerance, conflict resolution and respect for diversity is needed. Coaches also need training so that they can teach the concept of multiculturalism in more depth. The integration of multicultural education is expected to form Christian teenagers who are strong in faith and have social awareness to coexist in diversity according to God's holistic mission.